(untitled) (Informatica, 2019)
This paper reviews the main current situation of digital rural tourism with intelligent backgrounds, so as to accurately grasp the current status of the definition of digital rural tourism. This paper analyzes the basic theory of rural tourism development model, and combines the development model theory, and uses logical methods to analyze the development pattern of digital rural tourism with intelligent background, and provides guidance for the development of digital rural tourism in China.